A Law Enforcement Perspective on Football Supporter Riots in Indonesia (Comparative Analysis of The Old and New Criminal Codes) - Wildan Alfa Sina; Muchamad Iksan (Proceeding International Conference Restructuring and Transforming Law, 2024)
Anarchist attitudes are one of the classic problems in managing the football league in Indonesia, which will continue to emerge every year if it is not followed up firmly. The phenomenon of widespread football supporters rioting has caused anxiety among the public. Law enforcement is an important instrument in dealing with this problem. This article examines the comparison between the old Criminal Code and the new Criminal Code in law enforcement against football supporter riots in Indonesia. The research method used is the normative juridical method using library research. Analysis shows that the new Criminal Code has the potential to increase the effectiveness of law enforcement. Challenges faced include identification of perpetrators, gathering strong evidence, involvement of law enforcement officials, and legal awareness. Suggested solutions include strengthening regulations, strict law enforcement, increasing education, and collaboration between stakeholders. Thus, the new Criminal Code opens up better opportunities for law enforcement against football supporter riots. However, additional efforts are needed to overcome the various challenges faced.